Luxury Store Attributes and Customer Relationships - Exploring the Role of Luxury Brand Types - Islam, Mohammad Majedul; Rabbanee, Fazlul; Quaddus, Mohammed (2019)
The luxury store attributes (LSA) serve as resources to enrich artistic presentation and aesthetic appeal of a luxury brand, which are strong driving factors to develop relationship with customers. However, no research thus far investigated the relationships between LSA and customer relationship behaviour. Drawing on the social exchange theory, this study investigates the effects of LSA on customer relationship behaviour such as participation and loyalty. It also explores how such effect varies due to types of luxury brands. Data for the study was collected through qualitative in-depth interviews conducted among sixteen academic staff, administrative staff and post-graduate students. The findings revealed that LSA has positive effect on customer participation and brand loyalty. Further, such effect is found to be influenced by types of luxury brands (aspirational vs affordable). These findings offer significant theoretical and managerial implications, as outlined in the paper.